FEATURES OF COURT INVESTIGATION AT LAY COURT - A. A. Khaidarov (Russian Journal of Economics and Law)
The article views the problems occurring during court investigation at lay courts. The author analyzes the RF Criminal-Procedural Code articles concerning the investigation of the defendant's personality at lay court.